IMPLEMENTASI STRUKTUR TIGA BABAK DALAM PENULISAN NASKAH VIDEO FEATURE “OGAH JADI PETANI: PEWARIS YANG KRISIS” - Renaldi, Muhammad; Saepudin, Encang; Gumilar, Gumgum (Program Studi Komunikasi dan Penyiaran Islam, 2025)
The scriptwriter plays a crucial role in determining the idea and concept of the story that will be translated into the video script. As a key element in video production, including video features, the scriptwriter is responsible for structuring the foundational story that will serve as a guide for the entire production team in developing supporting elements of the video. The creativity of the scriptwriter is reflected in the final work, which ultimately produces a high-quality and watchable video. The aim of this research is to explain the implementation of the Three-Act Structure in the scriptwriting of the video feature titled “Ogah Jadi Petani: Pewaris yang Krisis”, which includes Act 1, Act 2, and Act 3. The synthesis analysis of Act 1 (Setup) is described by the introduction of the situation and explanation of the issues raised. In Act 2 (Confrontation), the character is shown facing various challenges and obstacles. Meanwhile, in Act 3 (Resolution), the implementation of the Three-Act Structure culminates in a climax with well-organized narration, making the work a cohesive whole. In conclusion, the scriptwriter successfully conveyed the implementation of the Three-Act Structure in the scriptwriting of the video feature “Ogah Jadi Petani: Pewaris yang Krisis”